The Implementation of Telling a Story and Storytelling Video on Students’ Motivation in Learning English - Rezky Uspayanti; Wahyuniar; Ray Suryadi (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2022)
This research aimed to find out the students’ motivation in learning English with the use of storytelling. The research was categorized as descriptive qualitative research. The research was done in Junior High School YAPIS Merauke which focused on eighth grade in 2021. The sample was chosen by using cluster random sampling. The sample focused on VIII. A which consisted of 21 students. The data was taken through observation using an observation checklist and interview. The observation checklist included 20 statements and the interview included 8 questions related to motivation and storytelling. The result of observations and interviews showed that the students' motivation increased in learning English. For treatment step, students were motivated to ask and respond to the questions given. Thus, most students enjoy learning English through videos, students are interested in the teaching materials provided, and some students understand the material better by presenting using videos, concluding the material, and understanding by presenting the material through the zoom application. In addition, by telling stories, most students are more flexible in retelling the contents of the story and they are also motivated by using such a way.